Estudo sobre interatividade no curso de licenciatura em Matemática da UAB/UFS - Pimenta, Elkelane da Silva Paiva (2020)
Information and Communication Technologies (ICT) have provided education with new perspectives and teaching possibilities, such as the exponential growth of Distance Education (DE), driven by the internet. Through this educational modality, many teachers are trained to enter or remain in teaching, a relevant fact to realize its importance and impacts on present and future education. In this context, the present study aims to investigate interactivity in the Virtual Learning Environment (VLE) in the Mathematics degree course offered at a distance by the Open University of Brazil (OUB) through the Federal University of Sergipe (FUS). To support the research, several authors were mentioned, such as Belloni (2015), Castells (1999), Silva (2012), Primo (2011), Vasconcelos (2017) among others. The research was carried out in the Virtual Learning Environment (VLE), Moodle platform, from the Higher Distance Education Center (HDEC), identifying design issues, available resources and potentials existing in this environment. Tutors who used VLE during the investigation period also participated. The data of this research related to the interviews were evaluated in the light of the theory of content analysis by Bardin (2011), as well as other data related to the environment itself were weighted using an evaluation instrument created based on the research and based on the ideas of the authors already mentioned. This stage of data analysis compares two VLE, one used by HDEC and the other by the Department of Mathematics (DM), called the Base platform, both used in the Distance Mathematics course, pointing to their main differences, similarities and possibilities for improvement. The results show relevant points that can be used as indicators of changes and improvements, also indicating how interactivity occurs and what its potential, within the VLE used, in the formation of teachers in Mathematics. Therefore, with the results of this research we seek to propose a reflection on the importance of interactivity in VLE and its contribution to quality in education.